Information technology. Telecommunications and information exchange between systems. List of standard data link layer protocols that utilize High-Level Data Link Control (HDLC) classes of procedures and list of standardized XID format identifiers and private parameter set identification values. (15th January 1995) - British Standards Institution
No abstract available